HUBUNGAN PERAN KELUARGA DAN TINGKAT STRES TERHADAP KADAR GULA DARAH PADA LANSIA DENGAN DIABETES MELLITUS TIPE II: DIABETES MELLITUS TIPE II - Wahdi, Achmad; Puspitosari, Dewi Retno; Prasetyawan, Fendy; Karingga, Devangga Darma; Ramayanti, Eva Dwi (LPPM STIKes Bahrul Ulum Jombang, 2024)
Elderly is an unavoidable aging process that will decrease body function. One is the decline in adapting to stress on the environment or illness suffered. This study aims to determine the relationship between the role of the family and the level of stress on blood sugar levels in elderly patients Diabetes mellitus in Puskesmas Bunten Barat Ketapang. This research uses observational analytic design with cross sectional approach. Population of all elderly Diabetes mellitus type 2 and elderly family. The sample size of 30 respondents was taken by simple random sampling technique. Independent variable in this research is family role and stress level. Dependent variable is blood sugar level. The data collection instrument used the family role questionnaire, the DDS (Diabet Distress Scale) questionnaire and the blood sugar glucose observation sheet. Data were analyzed with Exact Fisher test with significance level α = 0,05. The result showed almost half (43,3%) family role enough, almost half (43,3%) heavy stress respondent level, most (63,3%) abnormal sugar level. Exact Fisher test results obtained ρ = 0.001 <α for the relationship of family roles and blood sugar levels means there is a relationship role of the family with blood sugar levels. The relationship of stress level and blood sugar levels obtained ρ = 0,000 <α means there is a relationship between stress levels with blood sugar levels. Family role is expected in caring for family members, especially the sick including elderly. It is expected that families play a role in diabetes care and is expected for the elderly can control the stress they are experiencing problems faced.. Keywords: Family Role, Stress Level, Sugar Level